Družbeno-ekonomska merila odločanja o gojenju gensko spremenjenih organizmov v Sloveniji - Poler Kovačič, Melita (Družboslovne razprave, 2011)
According to the European Commission's proposed regulation from 2010, European Union member states can also restrict or prohibit the cultivation of genetically modified organisms (GMOs) in their territory on the basis of the socio-economic factors of the impact of GMOs. The paper presents reference approaches to designing and arguing the socio-economic impact of GMOs and reveals significant variation between them. An agreement on a comprehensive, empirically supported and mutually acceptable set of factors that would allow integration into the EU's regulatory framework has not yet been achieved. Slovenia is stepping into the process of designing relevant socioeconomic factors with negative public attitudes to the cultivation of GMOs, related restrictive legislation, and the natural and structural characteristics of agriculture which at the outset restrict the possibility to grow GMOs. In the paper, we propose a set of seven socio-economic factors which reflect specific characteristics of the Slovenian agricultural and social environment, and which could serve as a platform for public debate on this issue.
Keywords: Gensko spremenjeni organizmi; Transgenic organisms; Kmetijska politika; Agricultural policy; Družbeni vpliv; Social influence; Economic aspects; Ekonomski vidik; Slovenia; Slovenija; European Union; Evropska unija; zakonodaja